1999
DOI: 10.1046/j.1365-2141.1999.01266.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of human T‐lymphoid progenitor cells in CD34+CD38low and CD34+CD38+ subsets of human cord blood and bone marrow cells using NOD‐SCID fetal thymus organ cultures

Abstract: In contrast to myeloid and B‐lymphoid differentiation, which take place in the marrow environment, development of T cells requires the presence of thymic stromal cells. We demonstrate in this study that human CD34+, CD34+CD38+ and CD34+CD38low cells from both cord blood and adult bone marrow reproducibly develop into CD4+CD8+T cells when introduced into NOD‐SCID embryonic thymuses and further cultured in organotypic cultures. Such human/mouse FTOC (fetal thymic organ culture) thus represents a reproducible and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 52 publications
1
39
0
Order By: Relevance
“…Analysis of human cells collected from these thymic lobes showed that a high number of CD4 high human cells were recovered in lobes seeded with unfractionated cells (not shown) or CD79a ϩ -enriched CDw127 ϩ cells. A few (5%) CD4 high cells were double-positive (DP) CD4 ϩ CD8 ϩ cells ( Figure 5), which, as shown previously, 33 indicates T-cell differentiation; we cannot exclude, however, the contribution of non-T cells to the CD4 ϩ fraction. The low number of human cells collected from the thymic lobes precluded any extensive phenotyping and/or molecular analysis of T-cell receptor (TCR) rearrangement.…”
Section: Molecular Characterization Of Cd79amentioning
confidence: 52%
See 1 more Smart Citation
“…Analysis of human cells collected from these thymic lobes showed that a high number of CD4 high human cells were recovered in lobes seeded with unfractionated cells (not shown) or CD79a ϩ -enriched CDw127 ϩ cells. A few (5%) CD4 high cells were double-positive (DP) CD4 ϩ CD8 ϩ cells ( Figure 5), which, as shown previously, 33 indicates T-cell differentiation; we cannot exclude, however, the contribution of non-T cells to the CD4 ϩ fraction. The low number of human cells collected from the thymic lobes precluded any extensive phenotyping and/or molecular analysis of T-cell receptor (TCR) rearrangement.…”
Section: Molecular Characterization Of Cd79amentioning
confidence: 52%
“…Differentiation was evaluated in fetal thymic organ culture (FTOC) exactly as described previously in detail, 33 using E14 embryonic thymic lobes from NOD-SCID mice. Each lobe was incubated with either 10 000 unfractionated day 14 cultured cells, CDw127 ϩ CD79a ϩ CD19 Ϫ or CDw127 ϩ CD19 ϩ cells.…”
Section: Antibodiesmentioning
confidence: 99%
“…FTOC using murine thymus have enabled the identification of T cell progenitors, such as human CD34 ϩ cells (8,9). NOD/SCID mice transplanted with CD34 ϩ cells have been known to reconstitute these T cells in some cases (13).…”
Section: Discussionmentioning
confidence: 99%
“…An alternative approach, however, is also necessary, because this method requires human fetal tissue and is technically difficult. FTOC using murine thymus has been useful for the identification of T cell progenitors among human CD34 ϩ cells (8). However, the resultant T cells exhibit an immature phenotype, and their functional status has not been fully studied (9).…”
Section: T Lymphocyte Development From Hemopoietic Stem Cells (Hsc)mentioning
confidence: 99%
“…3 For limiting dilution experiments, harvested cells were co-incubated with NOD-SCID lobes and irradiated CD34 + cells as described before. 29 At the end of the culture, lobes were mechanically disrupted with a small tissue grinder to obtain a single cell suspension for evaluation with flow cytometry.…”
Section: Linmentioning
confidence: 99%